Faktor faktor yang mempengaruhi profitabilitas pada BPRS Serambi Mekah Kota Langsa - Rukaiyah Rukaiyah; Khairatun Hisan (Fakultas Ekonomi dan Bisnis Islam IAIN Langsa, 2023)
Bank is a financial institution that aims to make a profit. This profit is obtained from the management of funds from the community. Profitability is the bank's ability to generate / earn profits as measured by the ROA ratio. Return On Assets (ROA) is one way to measure the level of a bank's ability to make a profit. This study aims to examine profitability which is influenced by Earning Assets, Operating Income, Operational Expenses, and Profit Sharing for Fund Owners at PT BPRS Seurambi Mekah Kota Langsa. In this study using quantitative data because it analyzes data in the form of numbers / numerics. Data obtained based on the publication of Annual Bank, the analysis technique used is multiple linear regression analysis. The results of this study found that Productive Activities and Operational Expenses have a significant effect on profitability, and profit sharing on fund owners has no significant effect on profitability.